A pediatric nephrologist’s experience on real-time ultrasound-guided kidney biopsy - Simsek, Behcet (Journal of Surgery and Medicine, 2020)
Aim: Kidney biopsy is crucial in management of renal diseases. Biopsies in children have added difficulties. The aim of this study is to investigate our 5-year experience of real-time ultrasound (USG)-guided percutaneous renal biopsy (PRB). Methods: Institutional database of children who underwent PRB in a tertiary hospital between January 2015 and March 2020 were evaluated retrospectively. A single pediatric nephrologist performed all the biopsies using an automated spring-loaded biopsy gun under real-time USG guidance. Results: Thirty-two biopsies were performed in 17 males (53.1%) and 15 females (46.9%), and the median age of the children was 14.5 years. The most common indication for biopsy was nephrotic syndrome in 13 /32 children (40.6%). Median number of glomeruli obtained from biopsy specimens was 18 (min-max=7-54 glomeruli). A diagnosis was achieved in all cases (100%) by a histopathologist. The only complication observed in a 16-year-old boy was a self-limited gross hematuria (3.1%) episode with subcapsular hematoma. Conclusion: Real-time USG-guided PRB with an automated biopsy gun is an effective and safe technique, providing superior yield when performed by a pediatric nephrologist. Performing kidney biopsy is an essential tool in a nephrologist’s workshop.